MISIDENTIFIED FOR MORE THAN 50 YEARS, CROTALARIA ROSENII (LEGUMINOSAE, PAPILIONOIDEAE, CROTALARIEAE), A CULTIVATED SPECIES IN COLOMBIA AND ECUADOR - Fonseca-Cortés, Andrés (Phytotaxa, 2022)
Crotalaria rosenii (Pax) Milne-Redh. ex Polhill, an endemic species of the mountains of Ethiopia, is reported for the first time as an ornamental species. This taxon has been identified as C. agatiflora Schweinf. since 1952 in Colombia and 1982 in Ecuador, countries where it is continuously cultivated in parks, gardens and even in rural environments, which increases the propagule pressure and promotes a naturalization of this species. Crotalaria rosenii is easily recognized by the presence of bracteoles 1.0–1.2 × 0.2–0.3 cm, standard 5.0–5.5 × 4.0–4.6 cm, with the callosities glabrous, keel 5.8–6.0 cm length, with apex hooked, and ovoid slightly compressed seeds. I present a key to distinguish these two taxa, and comments related to the possible naturalization, distribution, and ecology of C. rosenii and C. agatiflora.